MOTIVATION OF FEMALE CRIMINATORS IN BANDUNG CLASS IIA WOMEN'S PRIVATE VOCATIONAL SCHOOL IN FOLLOWING THE INDEPENDENCE DEVELOPMENT PROGRAM - Sri Sulistijaningsih (Polteknik Ilmu Pemasyarakatan, 2020)
Prisoners in undergoing the crime of missing independence at the Penitentiary must be introduced to the community. Banyan Tree Protection Point.6). Prisoners must be given work and must be one with the community and support efforts to increase production. Bandung Women's Class IIA Penitentiary Institution is one of the Technical Implementation units of the Directorate General of Correctional Facility under the ranks of the West Java Province Ministry of Law and Human Rights office as a place to foster female prisoners in the field of independence fostering programs. Fostering the independence program is a form of fostering aimed at empowering female prisoners. It is hoped that they will be effective and efficient in empowering the family's economy, so that they can help a source of income for the family after being free from criminal punishment. The purpose of this study is to determine the motivation of women prisoners in Class IIA Bandung Women's Penitentiary in participating in a program to develop independence, find out the constraints of obstacles and provide solutions to overcome obstacles in the process of fostering Independence.